Avalanches and edge-of-chaos learning in neuromorphic nanowire networks - Joel Hochstetter (Nature Portfolio, 2021)
Neuromorphic nanowire networks are found to exhibit neural-like dynamics, including phase transitions and avalanche criticality. Hochstetter and Kuncic et al. show that the dynamical state at the edge-of-chaos is optimal for learning and favours computationally complex information processing tasks.